2009
DOI: 10.12693/aphyspola.115.1053
|View full text |Cite
|
Sign up to set email alerts
|

Intense Pulsed Electron Beams Application οf Modified Materials

Abstract: Intense pulsed electron beams have been applied for surface modification of materials in our laboratory for several years. An improvement of properties like wear, corrosion and oxidation resistance was found. Three different modification modes can be distinguished: rapid melting and solidification, surface alloying of coatings into the bulk and surface fusing of coatings to the bulk. All three surface treatment processes were investigated using the GESA (Gepulste Elektronen Strahl Anlage) facilities having fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The pulsed electron-beam facilities GESA I and GESA II were developed in cooperation between the Efremov Institute St Petersburg, Russia, and the Research Center Karlsruhe (FZK), Germany, for large area surface treatment [30]. The two facilities use the same principal set-up as detailed in [31]: electron injector of triode type with a multipoint explosive emission cathode, transport channel, treatment chamber, magnetic system, high-voltage generator, pulseduration control unit (PDCU), vacuum system, control rack, radiation protection and mechanical support. A schematic of the GESA facility and its capabilities are shown in figure 1, which is typical of such large scale facilities designed to do RTP with electron beams.…”
Section: Rtp Processing Using Electron Beamsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pulsed electron-beam facilities GESA I and GESA II were developed in cooperation between the Efremov Institute St Petersburg, Russia, and the Research Center Karlsruhe (FZK), Germany, for large area surface treatment [30]. The two facilities use the same principal set-up as detailed in [31]: electron injector of triode type with a multipoint explosive emission cathode, transport channel, treatment chamber, magnetic system, high-voltage generator, pulseduration control unit (PDCU), vacuum system, control rack, radiation protection and mechanical support. A schematic of the GESA facility and its capabilities are shown in figure 1, which is typical of such large scale facilities designed to do RTP with electron beams.…”
Section: Rtp Processing Using Electron Beamsmentioning
confidence: 99%
“…A schematic of the GESA facility and its capabilities are shown in figure 1, which is typical of such large scale facilities designed to do RTP with electron beams. Recently, Weisenburger [31] presented the surface modification materials using the above facilities and reported that the changes in microstructure led to hardening of gears and increased their wear resistance. A decrease in the oxidation rate of high temperature alloys is also reported.…”
Section: Rtp Processing Using Electron Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron beams are generally used for the generation of X radiation. The field of their application covers a wide range of scientific and technical studies as well as medical purposes [1][2][3][4]; the electron beams are used for sterilization, heating in medicine and for heating plasma in magnetic traps for scientific purposes, as well as in original directions (for example: synthesis of nanosized metal oxides [5][6][7], plasma chemical conversion of waste uranium hexafluoride [8], treatment and disinfection of industrial and domestic waste water [9][10]). The application of electron beams in different directions is determined by the high energy efficiency.…”
Section: Introductionmentioning
confidence: 99%